2019
DOI: 10.20402/ajbc.2019.0299
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Management according to the Characteristics of Beauty Service Workers

Abstract: Purpose: The present study investigates human resource management in the beauty service industry based the characteristics of workers. Methods: Data were collected from the beauty service industry and analyzed using Statistical Package for the Social Sciences (SPSS) 22.0. Frequency analysis, factor analysis, reliability analysis, independent sample t-test, and one-way ANOVA were used for data analysis. Results: There were significant differences in human resource management based on gender, age, marital status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Due to the consistent progress of aspects of service, the beauty service industry has become a greater part of modern life for people who pursue both beauty and individuality. It has also developed into an attractive industry with consistent purchases [23]. Figure 1 displays the sales of the beauty service industry in 2017 with 6.6025 trillion won where 5.2366 trillion won, 79.31% of the industry total, is hairstyling.…”
Section: Global Beauty Industry and K-beautymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the consistent progress of aspects of service, the beauty service industry has become a greater part of modern life for people who pursue both beauty and individuality. It has also developed into an attractive industry with consistent purchases [23]. Figure 1 displays the sales of the beauty service industry in 2017 with 6.6025 trillion won where 5.2366 trillion won, 79.31% of the industry total, is hairstyling.…”
Section: Global Beauty Industry and K-beautymentioning
confidence: 99%
“…Kim and Lee [28] found a significant relationship between employee job satisfaction with the employee's customer orientation and the impact of the relationship on the long-term business performance of beauty shops in South Korea. In addition, Park et al [29] suggested that active and systematic managerial support for junior workers is needed to achieve sustainability in the beauty service industry. Therefore, establishing effective organization management systems and planning distinctive strategies would secure competitive advantages.…”
Section: Previous Studies On the Beauty Servicementioning
confidence: 99%